Pan‐cancer analysis of alternative splicing regulator heterogeneous nuclear ribonucleoproteins (hnRNPs) family and their prognostic potential. Issue 19 (11th September 2020) - Li, Hao; Liu, Jingwei; Shen, Shixuan; Dai, Di; Cheng, Shitong; Dong, Xiaolong; Sun, Liping; Guo, Xiaolin
Abstract: As the most critical alternative splicing regulator, heterogeneous nuclear ribonucleoproteins (hnRNPs) have been reported to be implicated in various aspects of cancer. However, the comprehensive understanding of hnRNPs in cancer is still lacking. The molecular alterations and clinical relevance of hnRNP genes were systematically analysed in 33 cancer types based on next‐generation sequence data. The expression, mutation, copy number variation, functional pathways, immune cell correlations and prognostic value of hnRNPs were investigated across different cancer types. HNRNPA1 and HNRNPAB were highly expressed in most tumours. HNRNPM, HNRNPUL1, and HNRNPL showed high mutation frequencies, and most hnRNP genes were frequently mutated in uterine corpus endometrial carcinoma (UCEC). HNRNPA2B1 showed widespread copy number amplification across various cancer types. HNRNPs participated in cancer‐related pathways including protein secretion, mitotic spindle, G2/M checkpoint, DNA repair, IL6/JAK/STAT3 signal and coagulation, of which hnRNP genes of HNRNPF, HNRNPH2, HNRNPU and HNRNPUL1 are more likely to be implicated. Significant correlation of hnRNP genes with T help cells, NK cells, CD8 positive T cells and neutrophils was identified. Most hnRNPs were associated with worse survival of adrenocortical carcinoma (ACC), liver hepatocellular carcinoma (LIHC) and lung adenocarcinoma (LUAD), whereas hnRNPs predicted better prognosis in kidney renal clear cell carcinoma (KIRC) and thymoma (THYM). The prognosis analysis of KIRC suggested that hnRNPs gene cluster was significantly associated with overall survival (HR = 0.5, 95% CI = 0.35‐0.73, P = 0.003). These findings provide novel evidence for further investigation of hnRNPs in the development and therapy of cancer in the future.